2020
DOI: 10.1021/acsomega.9b04392
|View full text |Cite
|
Sign up to set email alerts
|

Sulfenate Esters of Simple Phenols Exhibit Enhanced Activity against Biofilms

Abstract: The recalcitrance exhibited by microbial biofilms to conventional disinfectants has motivated the development of new chemical strategies to control and eradicate biofilms. The activities of several small phenolic compounds and their trichloromethylsulfenyl ester derivatives were evaluated against planktonic cells and mature biofilms of Staphylococcus epidermidis and Pseudomonas aeruginosa. Some of the phenolic parent compounds are well-studied constituents of plant essential oils, for example, eugenol, menthol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 103 publications
0
8
0
Order By: Relevance
“…AM derivatives were typically more potent than their corresponding parent phenols against planktonic cells, apart from 1/2k against S. epidermidis (Table 1). We have previously shown that the lipophilic phenols 1d (in particular) and 1e are unusually potent toward S. epidermidis (Walsh et al., 2020). The observation that 2d exhibits a lower potency compared to 1d toward both bacteria may simply be a case where the exceptional activity of the parent phenol is ineffectively expressed in its AM.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…AM derivatives were typically more potent than their corresponding parent phenols against planktonic cells, apart from 1/2k against S. epidermidis (Table 1). We have previously shown that the lipophilic phenols 1d (in particular) and 1e are unusually potent toward S. epidermidis (Walsh et al., 2020). The observation that 2d exhibits a lower potency compared to 1d toward both bacteria may simply be a case where the exceptional activity of the parent phenol is ineffectively expressed in its AM.…”
Section: Resultsmentioning
confidence: 98%
“…Exceptions to the predominant trend are 1/2k , 1/2g , and 1/2e where parent and AM shared the same MBEC against S. epidermidis and compound 2d where the AM was less potent against both bacteria (Table 2). In the cases of 1/2d , 1/2e , and 1/2k (a chlorophenol), the parent phenol already possessed superb activity, with 2d and 2e sharing a highly hydrophobic substituent at the 4‐position (vide supra; Walsh et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…For the effective development and application of such novel agents, it is, however, important to have previously compared their efficiency with the classically applied ones. Although several studies have been published in recent years related to the anti-biofilm action of many plant compounds, including CAR, THY and EUG, against various bacteria [33][34][35][36][37], including staphylococci [38][39][40][41], very few of them have compared their actions with those of standard chemical antimicrobials [42][43][44][45][46]. In addition, and to the best of our knowledge, no other study has been published comparing in parallel the efficiency of these three common plant-derived terpenoids (i.e., CAR, THY, and EUG) and of BAC against both planktonic and biofilm Staphylococcus bacteria or of other species.…”
Section: Introductionmentioning
confidence: 99%
“…The Gram-negative bacterium selected for this study, Pseudomonas aeruginosa, is opportunistic, exhibits multi-drug resistance, and has a pronounced propensity to form biofilms. The Gram-positive bacterium selected for this study, Staphylococcus epidermidis, has the ability to form biofilms and has been implicated in chronic urinary tract infections, as well as persistent infections on medical devices [26][27][28]. Staphylococcus epidermidis strain ATCC 35984 was chosen as a representative Grampositive organism with well-documented biofilm-forming ability.…”
Section: Biological Evaluationmentioning
confidence: 99%
“…The minimum inhibitory concentrations (MICs) of all compounds against S. epidermidis and P. aeruginosa were determined using a modified 96-well plate assay previously described by Walsh et. al., [26][27][28]. In short, Costar polystyrene 96-well plates were prepared with 150 µL of TSB and serial dilutions of the compound in dimethyl sulfoxide (DMSO).…”
Section: Microbiologymentioning
confidence: 99%